Ladies' orchestras and music-as-performance in fin-de-siècle Britain. Issue 1 (1st January 2023) - Draucker, Shannon
ABSTRACT: This article traces the emergence of a curious musical phenomenon in fin-de-siècle Britain: the ladies' orchestra. As British music conservatories began to open to women in the 1870s and 1880s, and the violin gradually became a more "acceptable" instrument for women to play, ladies' orchestras offered female musicians – still excluded from the country's major symphony orchestras – opportunities to perform in public and sometimes even earn a living. Analyzing responses to ladies' orchestras in the British periodical press, this article shows that ladies' orchestras invited Victorian audiences to think about classical music in new ways. Ladies' orchestras, though niche, fundamentally shifted the sensual experience of the orchestra concert, transforming it from a staid, solemn event centered on "the music itself" to a multisensorial spectacle, complete with colorful costumes, dazzling stage settings, and dynamic displays of musical vigor and passion. Ladies' orchestras embraced what musicologists now call a "performance-based" approach, one that tunes into the spatial, temporal, sensory, kinesthetic, and affective dimensions of classical music.